Antimicrobial central venous catheters do not reduce infections in pre-term babies. (4th November 2019) - Cook, Rob; Fortescue-Webb, Duncan; Martin, Rosie
The study: Gilbert R, Brown M, Rainford N et al. Antimicrobial-impregnated central venous catheters for prevention of neonatal bloodstream infection (PREVAIL): an open-label, parallel-group, pragmatic, randomised controlled trial. Lancet Child Adolesc Health 2019;3:381-90. The study was funded by the NIHR Health Technology Assessment programme (project number 12/167/02). To read the full NIHR Signal, go to https://discover.dc.nihr.ac.uk/content/signal-000782/antimicrobial-central-venous-catheters-for-pre-term-babies-do-not-reduce-infections